Developing Critical Thinking of Grade 10 Students through Inquiry-Based STEM Learning - Onsee, Peeradon; Nuangchalerm, Prasart (Jurnal Penelitian dan Pembelajaran IPA, 2019)
Thematic approach in education is a way of holistic view in modern instructional practices. The 21st century learning needs students have ability and necessary skills, especially thinking critically than content focused. This action research aims to enhance critical thinking and learning achievement of grade 10 students through inquiry-based STEM learning. Twenty first students were participated by who had mean score lower than 70 percent of critical thinking. The research instruments consisted of 6 lesson plans, 20 items of critical thinking test with 4-multiple choice, interviewing form in teaching and learning environments, and observation during lesson plans implementation. Data were gathered and analyzed by descriptive statistics. The result showed that students who learned through inquiry-based STEM learning can increase their critical thinking to meet the criterion. Qualitative data indicated that they need more improvement in the diversity of learning methods as well as STEM education. Suggestion needs students to design and criticize in their working assignment.